American-Cuban baseball diplomacy as an example of actions aimed at a rapprochement between hostile countries (Economic and Political Thought, 2016)
The aim of the research undertaken in the article is to analyse one of theexamples of sports diplomacy directed at rapprochement between two hostilestates – the United States and Cuba. There have been a number of sportsexchanges in baseball between the two states, which are the object of theresearch. The undertaken research is empirical. It is a case study concerningone of the examples of positive sports diplomacy. A decision-making methodhas been employed in order to analyse the data acquired from historicalworks, American documents and media coverage. As a results of the researchit was determined that American-Cuban baseball diplomacy was only partiallysuccessful in bringing the two hostile states closer. Similarly, the choice ofbaseball as a tool of rapprochement had both positive and negative effects.It was also acknowledged that in fact baseball diplomacy between the USAand Cuba integrated both positive and negative elements of sports diplomacy.